A protocol for a randomized clinical trial assessing the efficacy of hypertonic dextrose injection (prolotherapy) in chronic ankle instability - Regina Wing Shan Sit; Ricky Wing Keung Wu; Samuel Ka Kin Ling; Bo Wang; Dicken Cheong Chun Chan; Benjamin Hon Kei Yip; Samuel Yeung Shan Wong; Kenneth Dean Reeves; David Rabago (Trials, 2022)
Abstract Background Lateral ankle sprain (LAS) is a common injury. Conservative care is not uniformly effective. Chronic ankle instability (CAI) results in up to 70% of patients with LAS in the physically active population. LAS, together with subsequent osteochondral lesions and pain in many patients, leads to the development of post-traumatic osteoarthritis, resulting in a substantial direct and indirect personal and societal health burden. Dextrose prolotherapy (DPT) is an injection-based therapy for many chronic musculoskeletal conditions but has not been tested for CAI. This protocol describes a randomized controlled trial to test the efficacy of DPT versus normal saline (NS) injections for chronic ankle instability (CAI). Methods and analysis A single-center, parallel-group, randomized controlled trial will be conducted at a university-based primary care clinic in Hong Kong. A total of 114 patients with CAI will be randomly allocated (1:1) to DPT and NS groups. The primary outcome will be the Cumberland Ankle Instability Tool scores at 1 year. The secondary outcomes will be the number of re-sprains in 1 year, the Star Excursion Balance Test, the 5-level of EuroQol 5-dimension questionnaire, and the Foot and Ankle Ability Measure. All outcomes will be evaluated at baseline and at 16, 26, and 52 weeks using a linear mixed model. Discussion We hypothesized the DPT is a safe, easily accessible, and effective treatment for patients with CAI. This RCT study will inform whether DPT could be a primary non-surgical treatment for CAI. Trial registration Chinese Clinical Trial Registry ChiCTR2000040213 . Registered on 25 November 2020.